ENVIRONMENTAL PROBLEMS OF ZINC-BASED ELECTROPLATING - Балкембай, Аққу; Сдикова, Гулия (Вестник ЗКУ, 2023)
The environmental problem of electroplating is the pollution of the environment with heavy metals. Since most metals containing electroplating coatings are found in tap water, there is a high probability of the presence of heavy metal ions, inorganic acids and alkalis, surfactants and highly toxic waste in it. Environmental protection consists in the application of modern high-tech technologies with local purification at various stages of technological processes, physico-chemical methods for controlling the composition of the reagents used. Production of zinc-based electroplating by electrolytic, physico-chemical methods, production in a special experimental sequence. The solution of electroplating production is possible only by an integrated approach, including legislative acts and their execution. The thickness of the resulting zinc coating of the metal surface was obtained electrochemically and is 40 microns.